Information Policy of the Enterprise as the Basis for the Reproduction of Human Potential in the Structure of Public Social Interaction - TSYPKO, Victoria V.; ALIEKSIEIEVA, Kateryna I.; VENGER, Iryna A.; TAVOLZHANSKYI, Oleksii V.; GALUNETS, Nataliya I.; KLYUCHNIK, Alona V. (Journal of Advanced Research in Law and Economics, 2019)
The paper determines that human potential at the present time allows expanding the economic opportunities of the state and individual spheres of expanded reproduction in the social and economic environment. The work is based on the notion that human potential is able to determine the possibilities for the development not only of a specific organization, but of the entire social and economic education as a whole. The authors consider the technology of the information space and formation of the information policy structure on its basis to be the foundation for integration into the corporate environment of human potential principles. The article reveals not only the purpose of the information policy, but also its dissemination on the basis of integration of the economic situation into the overall structure of social development. The novelty of the work is the very technology of human potential implementation, its forms and methods of application within the development of the technological environment. Within the framework of the article, the authors also determine that the calculation of human potential can also be represented as a system of capitalization of production or a factor of increasing economic market indicators. The prospect of using capital in the structure of social development is the information environment, which is determined by the need to create broader information of the social and economic formation about the activities of the enterprise